Oroxin A reduces oxidative stress, apoptosis, and autophagy and improves the developmental competence of porcine embryos in vitro. Issue 10 (12th July 2022) - Liu, Rong‐Ping; Wang, Xin‐Qin; Wang, Jing; Dan, Luo; Li, Ying‐Hua; Jiang, Hao; Xu, Yong‐Nan; Kim, Nam‐Hyung
Abstract: Oroxin A (OA) is a flavonoid isolated from Oroxylum indicum (L.) Kurz that has various biological activities, including antioxidant activities. This study aimed to examine the viability of using OA in an in vitro culture (IVC) medium for its antioxidant effects and related molecular mechanisms on porcine blastocyst development. In this study, we investigated the effects of OA on early porcine embryo development via terminal deoxynucleotidyl transferase dUTP nick‐end labeling, 5‐ethynyl‐2′‐deoxyuridine labeling, quantitative reverse transcription PCR, and immunocytochemistry. Embryos cultured in the IVC medium supplemented with 2.5 μM of OA had an increased blastocyst formation rate, total cell number, and proliferation capacity, along with a low apoptosis rate. OA supplementation decreased reactive oxygen species levels while increasing glutathione levels. OA‐treated embryos exhibited an improved intracellular mitochondrial membrane potential and reduced autophagy. Moreover, levels of pluripotency‐ and antioxidant‐related genes were upregulated, whereas those of apoptosis‐ and autophagy‐related genes were downregulated by OA addition. In conclusion, OA improves preimplantation embryonic development by reducing oxidative stress and enhancing mitochondrial function.